Students' Writing Skills in Descriptive Text by Using Animated Movies in Tenth Grade Students of SMA N 9 Jambi City - Simatupang, Teresia Artati Oktaviani; Munawwaroh, Khidayatul; Fitri, Nurul (Universitas Batanghari Jambi, 2023)
Writing skills is the ability to express ideas or ideas into an essay. The purpose of this study was to determine the ability of FASE E1 SAJ class students at SMA N 9 Jambi City in writing descriptive text using animated movies. This research uses qualitative as the research design and descriptive as the research method. researchers used tests given to students as research instruments, then the results of these tests were assessed and analyzed. The population is class phase students at SMA N 9 Jambi city for the 2022/2023 academic year and the sample is 34 students in class fase E1 saj. the researcher uses a score rubric to help assess students' grades and written tests to obtain data. Based on research findings, indicators of students' writing abilities, namely content (63,23), organization (66,23), grammar (65,23), vocabulary (63,73), mechanics (76,47) are at a great level. In addition, students' scores in writing descriptive texts have an average score (66,91).